XML Does Real Programmers a Service. - Gorton, Ian (Computer (00189162), 2008)
The article discusses computer programmers, humorously examining the evolution of their trade from 1990 to 2008. "Real programmers," as the author terms computer programmers, changed from Fortran-only programmers to working in the distributed computing environment. Topics include interoperable, heterogeneous distributed systems, advanced pointer manipulation systems, and the ever-changing technical environment. Also discussed are quiche-eating computer programmers, employees with misplaced body piercings, and academic computer scientists who are a source of amusement to real programmers.